National Guidelines for Use of Animals in Research and Teaching - Uganda National Council for Science and Technology (Uganda National Council for Science and Technology, 2021)
The National Guidelines for Use of Animals in Research and Teaching establish Uganda's national ethical and regulatory framework for the humane use of animals in scientific research and teaching. Developed by the Uganda National Council for Science and Technology (UNCST), the guidelines provide standards for the acquisition, care, housing, handling, transportation, and use of animals while promoting the principles of animal welfare, scientific integrity, and responsible research conduct. The document outlines the roles and responsibilities of researchers, institutions, sponsors, and Institutional Animal Care and Use Committees (IACUCs) in ensuring ethical review, protocol approval, monitoring, and compliance with national and international best practices. It further addresses risk management, occupational health and safety, informed consent where applicable, community engagement, management of animal biological materials, collaborative research, data ownership and sharing, and mechanisms for reporting adverse events and non-compliance. By harmonizing animal research practices with internationally recognized ethical standards, these guidelines seek to safeguard animal welfare, enhance the quality and credibility of scientific research, strengthen regulatory oversight, and support responsible innovation and evidence-based decision-making in Uganda.